Language Politeness in the Comedy Show "Main Hakim Sendiri" - Yunus, Muhammad; Hakim, Khairul; Syakir, Akhmad (Journal of Literature Language and Academic Studies, 2024)
This study discusses the compliance and violation of the principle of language politeness in the comedy show Main Hakim Sendiri using Geoffrey Leech's politeness theory. The research data are dialog transcripts from two episodes with the highest number of viewers in March 2024. The descriptive qualitative approach and the simak-catat method were used for data collection. The results showed that violations were dominant with 55 data, especially on the maxims of agreement (35 data) and respect (14 data). Compliance was recorded as much as 24 data, dominated by the maxim of agreement (17 data). Politeness norm violations are used to create humor through sarcasm, irony, or explicit disagreement, while compliance serves to maintain the balance of social interaction. This research contributes to the study of pragmatics and practical recommendations for the entertainment industry.